3(y-3)=2y+9+y

Simple and best practice solution for 3(y-3)=2y+9+y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(y-3)=2y+9+y equation:


Simplifying
3(y + -3) = 2y + 9 + y

Reorder the terms:
3(-3 + y) = 2y + 9 + y
(-3 * 3 + y * 3) = 2y + 9 + y
(-9 + 3y) = 2y + 9 + y

Reorder the terms:
-9 + 3y = 9 + 2y + y

Combine like terms: 2y + y = 3y
-9 + 3y = 9 + 3y

Add '-3y' to each side of the equation.
-9 + 3y + -3y = 9 + 3y + -3y

Combine like terms: 3y + -3y = 0
-9 + 0 = 9 + 3y + -3y
-9 = 9 + 3y + -3y

Combine like terms: 3y + -3y = 0
-9 = 9 + 0
-9 = 9

Solving
-9 = 9

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| -5E-32+6E=19 | | -2(4+x)=25 | | 3.29-0.14x=5x-3.135 | | x^3+x^2+36*x-23=0 | | 7x+2y+(-8x)-3y= | | 40+s=61 | | 11=c-2 | | 4(x-1)-(3x+2)=2(x+7) | | 54x^2+40x=0 | | -1.80=4.0x-4.9(x^2) | | 5x-12=6x-16 | | -10-m=6m-10 | | x^3-19683=0 | | 9x-2(x-7)=2(x-2)+1 | | 5p=2p-4qforp | | -1.80=4.9x-4.9(x^2) | | -4=-5+x | | -2m+(-6m)= | | 10x-1=9x+8 | | 8(y+3)=4Y+32 | | 4x+(-3x)= | | -16-5z=51 | | 8(7+3)=4y+32 | | (x-8x-20)=(x+2) | | 2.22-3.34x=2x-4.555 | | 5y+3-2y-1=25 | | 3x+7=-8x+2 | | 58x^2+40x=0 | | 1.2x=1.4 | | 6-2x=-5x-9+14 | | 24m-16n= | | a+(a-9)=(a-7)-(a+2) |

Equations solver categories